Heparin‐coated cardiopulmonary bypass circuits selectively deplete the pattern recognition molecule ficolin‐2 of the lectin complement pathway in vivo. (February 2015) - Hein, E.; Munthe‐Fog, L.; Thiara, A. S.; Fiane, A. E.; Mollnes, T. E.; Garred, P.
Summary The complement system can be activated via the lectin pathway by the recognition molecules mannose‐binding lectin (MBL) and the ficolins. Ficolin‐2 exhibits binding against a broad range of ligands, including biomaterials in vitro, and low ficolin‐2 levels are associated with increased risk of infections. Thus, we investigated the biocompatibility of the recognition molecules of the lectin pathway in two different types of cardiopulmonary bypass circuits. Bloods were drawn at five time‐points before, during and postoperatively from 30 patients undergoing elective cardiac surgery. Patients were randomized into two groups using different coatings of cardiopulmonary bypass circuits, Phisio® (phosphorylcholine polymer coating) and Bioline® (albumin‐heparin coating). Concentrations of MBL, ficolin‐1, −2 and −3 and soluble C3a and terminal complement complex (TCC) in plasma samples were measured. Ficolin‐3‐mediated complement activation potential was evaluated with C4, C3 and TCC as output. There was no significant difference between the two circuit materials regarding MBL, ficolin‐1 and −3. In the Bioline® group the ficolin‐2 levels decreased significantly after initiation of surgery (P < 0·0001) and remained reduced throughout the sampling period. This was not seen for Phisio®‐coated circuits. Ficolin‐3‐mediated complement activation potential was reduced significantly in both groups after start of operation (P < 0·0001), whereas soluble C3a and TCC in the samples were increased (P < 0·0001). Ficolin‐2 was depleted from plasma during cardiac surgery when using heparin‐coated bypass circuits and did not reach baseline level 24 h postoperation. These findings may have implications for the postoperative susceptibility to infections in patients undergoing extracorporeal circulation procedures.